Study of the Exposure Rate from the Patients Injected with Radiopharmaceutical - Khanal, O. B.; Thapa, D.; Shah, B. R.; Mulmi, D. D.; Shah, A.; Adhikari, K.; Aryal, S. K. (International Journal of Applied Sciences and Biotechnology, 2014)
Nuclear medical imaging is done by injecting very small amount of radiopharmaceutical to the patient. The radiations from patients are detected by special type of Gamma camera that works with computer to yield precise pictures of the organs being imaged. The Technetium-99m, injected to renal scan patient, is the source of radiation to the individual near to patient. Thus the individual receives exposure from the patient. The exposure received by public in the imaging center from renal scan patients has been calculated. The exposure rate at the center is measured to check whether an individual near to the patient is below the internationally acceptable public dose limit. Public receive low amount of average exposure of (3.7 ± 1.7) mSv/h at 1m distance for delayed scan. However, public receives high amount of exposure of (234.4 ± 74.8) mSv/h at shorter distance of 0.25 m after immediate scan are not subject to dose limits of the occupational radiation worker. The exposure received at shorter distance is higher from the patients. Thus the hospitals providing radiation treatments must take account of the public dose limit for individuals accompanying treated patients. DOI: http://dx.doi.org/10.3126/ijasbt.v2i3.10972 Int J Appl Sci Biotechnol, Vol. 2(3): 336-341